2016
DOI: 10.1021/acs.inorgchem.6b01575
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency 1H NMR Chemical Shifts of SnII and PbII Hydrides Induced by Relativistic Effects: Quest for PbII Hydrides

Abstract: The role of relativistic effects on H NMR chemical shifts of Sn and Pb hydrides is investigated by using fully relativistic DFT calculations. The stability of possible Pb hydride isomers is studied together with their H NMR chemical shifts, which are predicted in the high-frequency region, up to 90 ppm. TheseH signals are dictated by sizable relativistic contributions due to spin-orbit coupling at the heavy atom and can be as large as 80 ppm for a hydrogen atom bound to Pb. Such high-frequency H NMR chemical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 75 publications
4
50
0
Order By: Relevance
“…In this example, the low-field shift could be explained with the influence of the heavy atom on the light atom chemical shift. [31] In the 119 Sn NMR spectrum of 7,t wo signals, ad oublet (1484 ppm, 1 J 119SnÀH = 550 Hz) and as inglet (1789 ppm), were found. The cationic Ar*Sn moiety exhibits the signala tl ower field, compared to the signalo ft he coordinated stannylene.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In this example, the low-field shift could be explained with the influence of the heavy atom on the light atom chemical shift. [31] In the 119 Sn NMR spectrum of 7,t wo signals, ad oublet (1484 ppm, 1 J 119SnÀH = 550 Hz) and as inglet (1789 ppm), were found. The cationic Ar*Sn moiety exhibits the signala tl ower field, compared to the signalo ft he coordinated stannylene.…”
Section: Resultsmentioning
confidence: 93%
“…For comparison, osmium complex [Cp*( i Pr 3 P)HOs=SnH(trip)] showed a 1 H NMR signal for the Sn−H moiety at 19.4 ppm. In this example, the low‐field shift could be explained with the influence of the heavy atom on the light atom chemical shift …”
Section: Resultsmentioning
confidence: 99%
“…18,19 Furthermore, the present authors have demonstrated that a four-component methodology is applicable to systems with up to 100 atoms, for calculation of nuclear magnetic resonance and electron paramagnetic resonance parameters. [20][21][22][23][24] Relativistic approaches to LR-TDDFT can be loosely classified using a combination of two criteria. The a) Electronic mail: stanislav.komorovsky@savba.sk first criterion is the method by which SOC and other relativistic effects are accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…At the first time HALA effect on proton NMR shielding constants was investigated as earlier as in the beginning of 1970s in hydrogen halides by Morishima et al The abnormal bias of the proton chemical shift in hydrogen halides (HX) ongoing from X = F to I, has been accounted for within the third‐order perturbation theory . After a while it has been established that relativistically induced proton chemical shift originates mainly from the spin‐orbit coupling (SOC) at the heavy atom . Spin‐orbit relativistic corrections to proton shielding constants, calculated by Morishima et al using semi‐empirical SCF‐LCAO MO approximation, were found to be 0.37 ppm for HF, 0.59 ppm for HCl, 2.98 ppm for HBr, and 8.21 ppm for HI molecules.…”
Section: Introductionmentioning
confidence: 99%
“…It has been noticed that 1 H NMR chemical shifts are highly sensitive to the presence of heavy atoms . At the first time HALA effect on proton NMR shielding constants was investigated as earlier as in the beginning of 1970s in hydrogen halides by Morishima et al The abnormal bias of the proton chemical shift in hydrogen halides (HX) ongoing from X = F to I, has been accounted for within the third‐order perturbation theory .…”
Section: Introductionmentioning
confidence: 99%